Digital bank licenses and consumer acceptance challenges in the banking sector of Malaysia - Aziz Ahmad, Jamal Ishak (2023)
In the internet age and the Industrial Revolution 4.0 (IR 4.0), banks are being forced to digitise their processes due to changing consumer habits and a new competitive environment. In the case of the Malaysian banking sector, Bank Negara Malaysia (BNM) has issued digital bank licences to five consortiums to develop digital-only bank services for the Malaysian market. The move has opened opportunities for FinTech companies and innovators to offer digital bank services in Malaysia while, at the same time, imposing new threats to the incumbent traditional banks. Since it is a new concept in the Malaysian banking sector, this study would attempt to understand the consumer acceptance challenges faced by digital-only banks. Understanding the market is important for the new players to better position themselves for greater penetration into the market and achieve their objective of reaching out to the underserved and unserved segments. The Technology Acceptance Model (TAM), Theory of Reasoned Action (TRA), Theory of Planned Behavior (TPB), Unified Theory of Acceptance and Use of Technology (UTAUT), and Diffusion of Innovation Theory (DOI) were the primary theoretical frameworks used in this study. This study also predicted that Trust, Perceived Safety, Brand Recognition, Perceived Ease-of-use and Cost have direct correlations with customers’ acceptance of digital bank services. To test this, quantitative data were collected by putting out an online survey through social media and messaging services. The positivist research philosophy and deductive research approach were adopted because they seemed to be the best ways to find answers to the questions posed by the research. The estimated findings of this study have shown that all proposed dependent variables have a statistically significant impact on the acceptance of digital bank services in the Malaysian banking sector. This study also encountered the fact that consumers' behaviour shifts to become more eco-conscious when there is unfavourable climate change. Therefore, this study also suggests that any future research model should incorporate environmental concerns.